A Public Health Argument Against Arming Teachers - David I. Swedler (New Prairie Press, 2018)
The peer-reviewed scientific literature does not support the idea that arming teachers will prevent school shootings. In this commentary, I draw on the criminal justice, injury prevention, and firearm safety literature to demonstrate how arming teachers will do more harm than good.